Perlindungan Hak Anak Di Luar Nikah: Studi Komparatif Antara Kompilasi Hukum Islam, Undang-Undang No. 1 Tahun 1974 Tentang Perkawinan, Dan Putusan Mahkamah Konstitusi No. 46/PUU-VIII/2010 - Nurrohmatul Jannah (Ta'lim : Jurnal Multidisiplin Ilmu, 2025)
Legal issues regarding the position of children born out of wedlock in Indonesia still leave disharmony between positive legal norms, religious norms, and constitutional jurisprudence. Law No. 1/1974 on Marriage and the Compilation of Islamic Law explicitly limit the civil rights of out-of-wedlock children to the mother and her family, reflecting a conservative normative view based on classical Islamic law. However, the Constitutional Court Decision No. 46/PUU-VIII/2010 reinterpreted Article 43 paragraph (1) of the Marriage Law and opened up space for the recognition of civil rights between out-of-wedlock children and their biological fathers on the basis of scientific evidence (such as DNA testing). This study aims to comparatively analyze the three sources of law to identify conceptual and normative differences, as well as to find common ground that can be the basis for harmonizing national family law. This research uses a qualitative method with a normative juridical approach through a literature study of laws and regulations, judicial documents (decisions of the Constitutional Court and Supreme Court), and scientific literature. The results show that there is no substantial integration between the three legal regimes, both in legislation and in judicial practice, resulting in legal uncertainty and discrimination against children's rights. This research emphasizes the urgency of reconstructing legal norms that can bridge the values of justice, child protection, and moral and religious principles. This article offers a harmonization scheme between Compilation of Islamic Law, the Marriage Law, and the jurisprudence of the Constitutional Court as a real contribution to the renewal of Islamic family law in Indonesia that is more inclusive and just.